Can green finance lead to green investment? Evidence from heavily polluting industries - Xiaona, Cui; Mohd Said, Ridzwana; Abdul Rahim, Norhuda; Mengjiao, Ni (Elsevier, 2024)
Green finance is crucial for promoting eco-friendly projects and mitigating climate-related financial risks. This study examines the impact of China's Green Finance Reform and Innovation Pilot Zone (GFPZ) policy on green investments by heavily polluting companies using the difference-in-differences (DID) method. Findings show GFPZ significantly increased corporate green investment (CGI). Mechanism analysis reveals GFPZ increased financial constraints of heavily polluting companies, compelling them to invest in green projects to improve their financing opportunities. Heterogeneity analysis highlights a greater impact on companies with substantial institutional investor shareholdings, high analyst coverage, extensive digital transformation, and rigorous regional environmental regulation. Further analysis shows that GFPZ notably boosts preventive green investment but not remedial green investment. Additionally, GFPZ amplifies CGI's positive effects on green innovation and carbon emission reductions. This study supports broader GFPZ policy implementation and provides strategies for polluting companies to pursue green development.